2013
DOI: 10.5195/d3000.2013.16
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the IADR Cariology Research, Craniofacial Biology, and Mineralized Tissue Groups Symposium, Iguaçu Falls, Brazil, June 2012: Gene-environment Interactions and Epigenetics in Oral Diseases: Enamel Formation and its Clinical Impact on Tooth Defects, Caries, and Erosion

Abstract: Characteristics of enamel may influence or modulate individual susceptibility to caries and erosion. These characteristics are defined during development, which is under strict genetic control, but can easily be modified in many ways by environmental factors. In the symposium, translational aspects of embryology, biochemistry, and genetics of amelogenesis were presented. The symposium provided unique insight into how basic sciences integrate with clinically relevant problems. The need for improved understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(20 reference statements)
0
3
0
1
Order By: Relevance
“…Susceptibility to dental caries and DE has been suspected to involve a genetic component . Recent studies have reported positive associations between genetic variation in amelogenin, tuftelin, and enamelin and higher caries experience .…”
mentioning
confidence: 99%
“…Susceptibility to dental caries and DE has been suspected to involve a genetic component . Recent studies have reported positive associations between genetic variation in amelogenin, tuftelin, and enamelin and higher caries experience .…”
mentioning
confidence: 99%
“…Dental caries remains a major issue to be solved in oral healthcare medicine [9][10][11] . Owing to the dietary changes, dental caries caused by carbonated beverages has been reported frequently in the recent decades 12) .…”
Section: Introductionmentioning
confidence: 99%
“…These events take place in a time‐ and space‐restricted fashion in rat incisors, and distinct zones of secreting, maturing, and mature enamel are observed according to the developmental stages of those teeth . Enamel covers dental crown and its altered development increases susceptibility to caries . Therefore, it is pertinent to study the effects of systemic diseases such as T1DM on the formation of that structure.…”
Section: Introductionmentioning
confidence: 99%